The psychological effects of research participation on people with dementia: findings from a German exploratory interview study - Seidel, Katja; Winiarski, Claudia; Thyrian, Jochen René; Haberstroh, Julia (Frontiers in Dementia, 2024)
The German National Dementia Strategy aims to engage people with dementia in research projects. However, the effects of such research participation on experience and behavior have been insufficiently explored. This study aimed to investigate the psychological effect of research participation on people living with dementia. In a qualitative, exploratory approach, guideline-based interviews were conducted with four persons with dementia who had served as co-researchers on an advisory board in a health services research study for eight months at that time. The analysis revealed predominantly positive effects of research participation at all levels of experience and behavior. Most effects were reported by the co-researchers on a cognitive level. Both the perception of being competent and of making a positive contribution to oneself and/or others are key effects of research participation. The main effects on an emotional level were joy and well-being and on a behavioral level were positive social contacts and social communication. Sadness and insecurity represent the sole negative effects. Nuanced focal points of effects among the individual interviews were found. The results align with existing research highlighting the positive effects of participation on people with dementia. Through advancing an interdisciplinary perspective on their research involvement, we advocate for heightened attention to this topic within the realm of psychology.